Hidden havens - Agrawal, David R. (CESifo, 2023)
An international tax haven is usually a low-tax jurisdiction that seeks to attract investment by foreign investors. But, there are many state and local jurisdictions within federal systems that set zero tax rates on personal or corporate income, consumption, property, and wealth in an effort to attract activity from other high-tax jurisdictions. I discuss whether subnational tax havens are distinct from intense tax competition. I conclude that in a federal system, the economic implications of the two may be similar, but the policy responses differ subtly. A survey of the empirical evidence on the effect of zero or very low tax rates indicates that the lowest tax jurisdiction may disproportionately benefit from non-real base shifting, but real and avoidance responses also arise in response to smaller tax differentials between non-havens. Turning to the corporate income tax, I discuss how legal rules such as formula apportionment, economic nexus, and incorporation rules influence tax competition and the avoidance behaviors of multistate companies.
10419/279324
Keywords: Graue Literatur; tax haven; tax competition; state and local public finance; regulatory competition; corporate charters